Clinical Features, Diagnosis, and Treatment of Primary Intraventricular Lymphoma: Insights From a Monocentric Case Series - Cheng, Lidong; Zhu, Hongtao; Wang, Jing; Wang, Guanghui; Ma, Xiaoyu; Zhao, Kai; Wang, Junwen; Shu, Kai (Frontiers in Neurology, 2022)
Objective Primary ventricular lymphoma (PVL) is an extremely rare and commonly misdiagnosed disease. Previous studies were predominantly case reports, and literature regarding the diagnosis and treatment of PVL is limited. Therefore, this study aimed to evaluate the characteristics of patients with PVL. Methods The data of patients with pathologically confirmed PVL were assessed. Epidemiological data, imaging findings, surgery, pathological results, and prognosis were retrospectively analyzed. A systematic review of relevant literature was also conducted. Results A total of eight patients with PVL were identified. The main symptom was increased intracranial pressure. Radiographically, five patients had single lesion and three had multiple lesions; typical findings on magnetic resonance imaging included hypointensity on T1- and T2-weighted imaging, adjacent brain edema, and homogeneous enhancement on contrast-enhanced T1-weighted images. Preoperatively, six cases were misdiagnosed and two cases did not get a definite diagnosis. Craniotomy was performed on all patients, and four achieved gross total resection. Hydrocephalus was relieved after surgical resection in four patients. Pathology revealed diffuse large B-cell lymphoma in all patients. Only one patient had a severe complication. A total of three patients received concomitant adjuvant treatment, whereas five patients refused any adjuvant therapy. At the time of follow-up, the median survival time of patients was 15 months. Conclusion Primary ventricular lymphoma mainly presented with symptoms of increased intracranial pressure and had several imaging characteristics for the diagnosis, but the condition still tends to be misdiagnosed. Surgical resection is a feasible treatment for patients with isolated nodules, especially those with acute obstructive hydrocephalus.